2018
DOI: 10.26444/aaem/90886
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium levels are associated with age-related cataract

Abstract: Due to a confirmed association between serum selenium levels and age-related cataract, low serum selenium levels may constitute a potential risk factor of age-related cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Serum selenium levels may differ among populations, depending on a number of factors, including, but not limited to, concentration of selenium in food. The concentration of this element in adult human blood serum depends on a person’s age [24]…”
Section: Selenium In Human Organismmentioning
confidence: 99%
“…Serum selenium levels may differ among populations, depending on a number of factors, including, but not limited to, concentration of selenium in food. The concentration of this element in adult human blood serum depends on a person’s age [24]…”
Section: Selenium In Human Organismmentioning
confidence: 99%
“…These studies were all able to indicate the close relationship between trace elements and cataract. However, recently Post et al found that low serum selenium levels maybe a risk factor of age-related cataract (31). This is in contrast to previous findings, perhaps indicating that the effect of selenium on cataract remains to be explored in a deeper step.…”
Section: Introductionmentioning
confidence: 79%
“…Human beings must consume around 55 micrograms of Se per day and not exceed the maximum limit of 400 micrograms per day [42]. The World Health Organization recommends a daily average intake of 55 µg of Se, while the recommendation is varied with age, gender, diet and geographic location [43]. The International Food and Nutrition Board has recommended an average daily intake of 40-70 µg Se and 45-55 µg Se for men and women, respectively, and 25 µg Se for children [2,44].…”
Section: Selenium Toxicity 231 Toxicity In Humans and Animalsmentioning
confidence: 99%